The Impact of Positive Affect on Falls and Fear of Falling in the Older Adult Population. - O'HALLORAN, AISLING (Oxford Journals, 2013)
Falling can have detrimental impacts both physically and psychologically on older people. Recent falls prevention guidelines from the American and British Geriatric Societies tend to minimise the psychological factors which contribute to falls risk. Previous studies have linked high positive affect to a reduced risk of stroke, myocar- dial infarction, mobility, disability, frailty and mortality. This study examined the impact of positive affect on falls and fear of falling.
Age and Ageing
British Geriatric Society (BGS), Annual Meeting
PUBLISHED
Harrogate, UK
Keywords: Ageing; Ageing